ANALISIS PEMANFAATAN RUANG PUBLIK PADA AKTIVITAS PENDUDUK DI PERMUKIMAN STUDI KASUS : PERMUKIMAN MLATEN KOTA SEMARANG - Anggita Nur Zahara Mariza; Ardiana Yuli Puspitasari (Universitas Islam Sultan Agung Semarang, 2017)
Mlaten settlement is one of the old neighborhoods in the city of Semarang that arrangement very concerned about the existence of a public space. The neighborhood was designed by Thomas Karsten in 1994 for low-income people with the design concept of